Epitope analysis of the collagen type V-specific T cell response in lung transplantation reveals an HLA-DRB1*15 bias in both recipient and donor. - Melissa R Keller; Lynn D Haynes; Ewa Jankowska-Gan; Jeremy A Sullivan; Vrushali V Agashe; Scott R Burlingham; William J Burlingham (PLoS ONE, 2013)
IL-17-dependent cellular immune responses to the α1 chain of collagen type V are associated with development of bronchiolitis obliterans syndrome after lung transplantation, and with idiopathic pulmonary fibrosis and coronary artery disease, primary indications for lung or heart transplantation, respectively.We found that 30% of the patients awaiting lung transplantation exhibited a strong cell-mediated immune response to col(V). Of these, 53% expressed HLA-DR15, compared to a 28% HLA-DR15 frequency in col(V) low-responders (p=0.02). After transplantation, patients with HLA-DR1 and -DR17, not -DR15, developed anti-col(V) responses most frequently (p=0.04 and 0.01 vs. controls, respectively). However, recipients of a lung from an HLA-DR15(+)donor were at significantly elevated risk of developing anti-col(V) responses (p=0.02) and BOS (p=0.03). To determine the molecular basis of this unusual pattern of DR allele bias, a peptide library comprising the collagenous region of the α1(V) protein was screened for binding to HLA-DR0101, -DR1501, -DR0301 (DR17) or to HLA-DQ2 (DQA1*0501: DQB1*0201; in linkage disequilibrium with -DR17) and -DQ6 (DQA1*0102: DQB1*0602; linked to -DR15). Eight 15-mer peptides, six DR-binding and two DQ-binding, were identified. HLA-DR15 binding to two peptides yielded the highest binding scores: 650 (where 100 = positive control) for p799 (GIRGLKGTKGEKGED), and 193 for p1439 (LRGIPGPVGEQGLPG). These peptides, which also bound weakly to HLA-DR1, elicited responses in both HLA-DR1(+) and -DR15(+) col(V) reactive hosts, whereas binding and immunoreactivity of p1049 (KDGPPGLRGFPGDRG) was DR15-specific. Remarkably, a col(V)-reactive HLA-DR1(+)DR15(neg) lung transplant patient, whose donor was HLA-DR15(+), responded not only to p799 and p1439, but also to p1049.HLA-DR15 and IPF disease were independently associated with pre-transplant col(V) autoimmunity. The increased risk of de novo immunity to col(V) and BOS, associated with receiving a lung transplant from an HLA-DR15(+) donor, may result from presentation by donor-derived HLA- DR15, of novel self-peptides to recipient T cells.